Outstanding UMP researchers, lecturers get RM160k cash awards - UMP, PNC
Thirteen categories of outstanding Universiti Malaysia Pahang (UMP) researchers and lecturers collectively took home RM160,000 cash prizes at the Cendekia Bitara 2009 Award ceremony held at the Bukit Gambang Resort City in early May.